A genomic comparison of two termites with different social complexity - Korb, Judith; Poulsen, Michael; Hu, Haofu; Li, Cai; Boomsma, Jacobus J.; Zhang, Guojie; Liebig, Jürgen (Frontiers in Genetics, 2015)
The termites evolved eusociality and complex societies before the ants, but have been studied much less. The recent publication of the first two termite genomes provides a unique comparative opportunity, particularly because the sequenced termites represent opposite ends of the social complexity spectrum. Zootermopsis nevadensis has simple colonies with totipotent workers that can develop into all castes (dispersing reproductives, nest-inheriting replacement reproductives, and soldiers). In contrast, the fungus-growing termite Macrotermes natalensis belongs to the higher termites and has very large and complex societies with morphologically distinct castes that are life-time sterile. Here we compare key characteristics of genomic architecture, focusing on genes involved in communication, immune defenses, mating biology and symbiosis that were likely important in termite social evolution. We discuss these in relation to what is known about these genes in the ants and outline hypotheses for further testing.